THU0026 CLONAL HAEMATOPOIESIS ASSOCIATED SOMATIC MUTATIONS IN RHEUMATOID ARTHRITIS. (2nd June 2020) - Tariq, F.; Alobaidi, B.; Xavier, M.; Mccorkindale, M.; Veltman, J.; Isaacs, J.; Pratt, A.; Anderson, A.; Collin, M.
Abstract : Background: Clonal haematopoiesis of indeterminate potential (CHIP) occurs when somatic mutations arise in myeloid neoplasia driver genes of haematopoietic progenitor cells, in the absence of overt cytopenia or dysplasia. The prevalence of CHIP increases with age. The most common genes affected by CHIP mutations in unselected populations are DNMT3A, ASXL1, and TET2. The presence of CHIP is linked to increased basal level of inflammation and a high risk of cardiovascular disease and all-cause mortality. Rheumatoid arthritis (RA) is one of the most common and debilitating multi-system autoimmune disorders, affecting up to 1% of adults in developed countries. The role of somatic mutations in the pathogenesis of autoimmune diseases is an unexplored area; therefore, we aimed to test the hypothesis that clonal haematopoiesis (CH) is associated with the incidence and severity of RA. Objectives: To evaluate the association of CH somatic mutation with severity of RA. Methods: 163 RA patients were recruited from the following cohorts: (i) E arly RA/treatment naive (n=31), (ii) R efractory RA - non-responders to Disease-Modifying Anti-Rheumatic Drugs (DMARDs) and biologics (n=48), (ii) F lare (n=41) vs R emission patients (n=43) –patients treated with DMARDs and withdrawn from treatment on achieving remission. Six months later, 50% relapse and 50% sustain remission. Single molecule molecular inversion probes (smMIPs) were used to screen for somatic mutations in 40 loci known to carry clonal haematopoiesis driver mutations (CHDMs). Whole exome sequencing was also performed on Flare/Remission patients (n = 84) to screen for CHDMs and other somatic mutations. In-house bioinformatics pipelines were used to call mutations from both the datasets. Results: We identified CH in RA with an overall prevalence of 14%. Twenty-four unique variants with a variant allele frequency (VAF) of 2-35% were found in ten genes including ASXL1, CBL, DNMT3A, GNAS, GNB1, PTPN11, PTPN12, SF3B1, TET2, and TP53. The number of unique patients carrying mutations in these genes are follows: refractory : n=12/48, flare : n=6/41, remission : n=4/43 and early RA : n=2/31. The majority of the mutations occurred in DNMT3A (n=6) followed by TP53 (N=4) and TET2 (n=3). Two variants with VAF of 15% were identified in two patients under the age of 30, both with clinically severe disease. In patients between the ages of 50-59 yrs., 60-69 yrs., and 70-79 yrs., CH was observed at 11% (4/35), 23% (11/46) and 17%(7/41), respectively. Conclusion: We here report the prevalence of CH in RA, affecting more patients with clinically advanced/refractory disease compared to those with early/less severe disease. Further study will be conducted to confirm the results. References: [1]Acuna-Hidalgo, R., Sengul, H., Steehouwer, M., van de Vorst, M., Vermeulen, S., & Kiemeney, L. et al. (2017). Ultra-sensitive Sequencing Identifies High Prevalence of Clonal Hematopoiesis-Associated Mutations throughout Adult Life. The American Journal Of Human Genetics, 101 (1), 50-64. doi: 10.1016/j.ajhg.2017.05.013 [2]NRAS - National Rheumatoid Arthritis Society. (2020). Retrieved 30 January 2020, from https://www.nras.org.uk/what-is-ra-article [3]Steensma, D., Bejar, R., Jaiswal, S., Lindsley, R., Sekeres, M., Hasserjian, R., & Ebert, B. (2015). Clonal hematopoiesis of indeterminate potential and its distinction from myelodysplastic syndromes. Blood, 126 (1), 9-16. doi: 10.1182/blood-2015-03-631747 Acknowledgments: National Institute for Health Research, United Kingdom Disclosure of Interests: Fareeha Tariq: None declared, Bilal Alobaidi: None declared, Miguel Xavier: None declared, Michael McCorkindale: None declared, Joris Veltman: None declared, John Isaacs Consultant of: AbbVie, Bristol-Myers Squibb, Eli Lilly, Gilead, Janssen, Merck, Pfizer, Roche, Arthur Pratt Grant/research support from: Pfizer, GSK, Amy Anderson: None declared, Matthew Collin: None declared